STREPTOCOCCIE ET RHUMATISME ARTICULAIRE AIGU - Asmae BOUKIOUD (Faculté de Médecine et de Pharmacie, Rabat - Thèse de médecine, 2021)
Keywords: Chronic rheumatic heart disease, Infection, Prophylaxis, Acute rheumatic fever, Streptococcus. Streptococci are gram-positive, catalase-negative, facultative anaerobic bacteria that require enriched media for growth. Their bacteriological diagnosis is made by direct method (identification of the germ) and by indirect method (antibody assay). The different species of the genus Streptococcus, pathogenic to humans, are the cause of several infections with variable severity. Acute rheumatic fever (ARF) is a post-streptococcal non-suppurative autoimmune inflammatory complication that occurs 2-4 weeks after an inadequately treated or untreated group A '-hemolytic streptococcal (GAS) infection. It affects mostly children between the ages of 5 and 14 years. It's a public health problem in Morocco, as well as in developing countries. Clinically, it's manifested by joint, cardiac, neurological and skin disorders. The prognosis is conditioned by the severity of the cardiac lesions which may evaluate to a chronic rheumatic heart disease (RHD). The risk of occurrence and aggravation of RHD is high with each recurrent episode of ARF. Its diagnosis is based on the Jones criteria recently modified in 2015 and which requires evidence of recent GAS infection. Echocardiography is essential for the diagnosis and followup of the disease. Therapeutic management of a rheumatic episode is based on anti-inflammatory drugs and antibiotic therapy. However, the best way to manage this pathology is through primordial prevention by the improvement of living conditions, as well as primary and secondary prevention.
Keywords: Cardite rhumatismale chronique; Infection; Prophylaxie; Rhumatisme articulaire aigu; Streptococcus